INTERVENTION PROGRAMME FOR THE PREVENTION OF BACK PAIN IN SCHOOLCHILDREN (Fiep Bulletin - online, 2013)
The main aim of this study was to design and assess an intervention programme to prevent back pain in schoolchildren aged 10 to 12. Methods: The study was conducted using 137 schoolchildren (71 boys and 66 girls), aged between 10 and 12, in Mallorca (Spain). The schools were chosen using stratified random sampling techniques, depending on the size, type and location of the schools. The questionnaire and data-collection method were first validated using the test-retest method. The intervention programme, which consisted of 6 one-hour sessions (4 theoretical and 2 practical), took place over a period of 4 weeks. Results: The questions referring to how heavy the schoolbags felt and whether carrying them was tiring gave similar results throughout the entire research process (p0.05 for another post-test three months later). Big improvements were achieved in raising the children's awareness that schoolbags are a risk factor in back pain, that some materials should be left in school, and that the weight of the schoolbags should be kept to a minimum (E
Keywords: back pain; schoolchildren; healthcare promotion